Hits and misses of bangladesh national health policy 2011 - Munzur-; Mainul Haque (Wolters Kluwer Medknow Publications, 2020)
National Health Policy (NHP) is a guiding principle for a country to identify the priority of health-care needs, resource allocations according to prioritization, and to achieve specific health-care goals. In addition, NHP is usually wide-ranging, all-inclusive plan that pursues each and every population to move on the road to better health. NHP targets to achieve universal health coverage and delivering quality health-care services to all at inexpensive cost, through a preemptive, protective, and prophylactic health-care program in all national and international developmental policy and planning. There are quite a few constituents that are valuable in executing health policy. These elements include novelty, technical compendium, communiqué, conglomerates, administration, supervision, and political awareness and promise. Health policies can be implemented at all levels of the government system. It helps in strengthening the overall health-care system of the country by effective public-private coordination and collaboration. In the year 1990, the Government of Bangladesh (GoB) tried to promulgate an NHP. Unfortunately, the attempt failed. The health-care system of the country operated without a policy until 2011. In the year 2011, the country's first health policy was published by the GoB. Though the country has have achieved excellent progress in providing health care, but yet Bangladesh has a few critical challenges that need immediate attention. In this article, we will try to address the pros and cons of the Bangladesh NHP 1990 and the positive aspects and challenges of NHP 2011.